2009
DOI: 10.1007/s00011-009-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of the prostatic stroma in chronic prostatitis/chronic pelvic pain syndrome

Abstract: We believe that new studies regarding chronic prostatitis should also be focused on prostatic stromal involvement in the inflammatory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Asymptomatic inflammatory . Type III chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), accounts for approximately 90% of prostatitis diagnoses, and was formerly known as chronic nonbacterial prostatitis . Atypical microorganisms have been identified as causative organisms of chronic prostatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic inflammatory . Type III chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), accounts for approximately 90% of prostatitis diagnoses, and was formerly known as chronic nonbacterial prostatitis . Atypical microorganisms have been identified as causative organisms of chronic prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Type III chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), accounts for approximately 90% of prostatitis diagnoses, and was formerly known as chronic nonbacterial prostatitis. 27 Atypical microorganisms have been identified as causative organisms of chronic prostatitis. T. vaginalis and Chlamydia trachomatis are frequent causative pathogens, 28 and T. vaginalis has been reported in 1% to 17% of patients with NGU.…”
Section: Infiltration and Degranulation Of Mast Cells In The Prostamentioning
confidence: 99%
“…The pSMC phenotypic changes are critical not only because they promote and sustain inflammation, but also because they alter stromal–epithelial interactions (Taboga et al, 2008). As a result, pSMCs have a protagonist role in the development, maintenance, and/or progression of prostatic diseases including prostatitis (Dellabella et al, 2009; Quintar et al, 2010), benign prostate hyperplasia (BPH), (Schauer and Rowley, 2011) and prostate cancer (Tuxhorn et al, 2001; Wong and Tam, 2002; Cunha et al, 2003). For instance, it has been reported that human stromal BPH cells express TLRs for different pathogens and actively contribute to chronic inflammation and prostatic hyperplasia by secreting proinflammatory cytokines and chemokines in response to TLR agonists (Penna et al, 2009).…”
mentioning
confidence: 99%
“…On digital rectal examination the prostate may be tender. During palpation patients may have tenderness of the pelvic floor muscles and a tight anal sphincter (Dellabella et al, 2009). …”
Section: Clinical Featuresmentioning
confidence: 99%